2010
DOI: 10.1590/s0103-64402010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors and hygiene habits of complete denture wearers

Abstract: In this study, a questionnaire was applied to patients from Ribeirão Preto Dental School, University of São Paulo, Brazil, to evaluate the hygiene methods and habits concerning the use of complete dentures, the age of dentures, and whether patients have been instructed on how to clean their dentures. The mean age of patients was 63.35 years, and most of them were females (82.08%). The results showed that 62.26% of the respondents had been using the same maxillary complete denture for more than 5 years, and 49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
4
42

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(173 citation statements)
references
References 17 publications
(16 reference statements)
7
111
4
42
Order By: Relevance
“…This finding was similar to other studies. [22][23][24][25] This may be due to (i) dentists lack of knowledge on denture cleaning method and (ii) patients might not follow the instructions given by dentists. 25 Majority of the previous denture wearers (59.7%) reported that they cleaned their denture 2 to 4 times daily.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was similar to other studies. [22][23][24][25] This may be due to (i) dentists lack of knowledge on denture cleaning method and (ii) patients might not follow the instructions given by dentists. 25 Majority of the previous denture wearers (59.7%) reported that they cleaned their denture 2 to 4 times daily.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, some studies have shown higher frequency of cleaning as Peracini et al who reported 73.58% cleaned their dentures 3 or more times daily and Pietrokvoski et al reported that 96% of patients reported cleaning their dentures 2 or more times per day. 23,26 Previous study by Hoad-Reddick et al reported that a combination of methods (brushing and soaking) was used more frequently. 22 Veres et al also found majority of patients (59%) brushed and immersed their dentures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jagger, Harrison (13) and Peracini et al (14) observed that the patients do not receive correct professional instructions on how to clean their dentures. They overclean the prostheses, using homecare products, which could cause harmful effects.…”
Section: Introductionmentioning
confidence: 99%